PEDAGOGICAL AND PSYCHOLOGICAL TECHNOLOGIES OF EDUCATION IN THE INTERPRETATION OF EASTERN CULTURE - Norkozieva Dilrabo Sheralievna; Raikhana Mahammadova (Galaxy International Interdisciplinary Research Journal, 2023)
This article examines the uniqueness of pedagogical and psychological views on education in Eastern culture and science, that is, to be healthy, to be resourceful, to have a strong and strong memory, to be sharp-minded and able to speak beautifully, education. - do not shy away from education, self-control, the use of pedagogical and psychological methods.